The role of speech rate in motivational communication in teacher-student interaction in physical education - Tuominen, Miika (2019)
As a way of combating the rising trend of physical inactivity, physical education has adopted inspiring students to lead a physically active life as one of its main goals. According to self-determination theory, achieving this outcome is more likely, if the students adopt autonomous motivation towards physical education. It is not surprising then that the nature of autonomy-supportive teacher-student interaction in physical education has been studied extensively in the recent years. What is surprising is that this research is almost exclusively focused on the verbal side of communication, seemingly forgetting the nonverbal side of human communication. However, there are some recent efforts focusing on the nonverbal aspects of autonomy-supportive communication in general that aim to address this gap by focusing on what is called motivational prosody. Prosody in general refers to properties and variations of voice that can be used to convey and infer meaning. It has been mainly studied in the fields of communication and speech research, but social and emotional prosody also count among the fields interested in the way we use our voice while communicating. Recent research in motivational prosody builds on these existing approaches while aiming to identify those prosodic properties of voice that are relevant or meaningful especially in motivational communication.